The education of Margot Sanchez - Rivera, Lilliam (Simon & Schuster BFYR, 2017)
Margot Sanchez is paying off her debts by working in her family's South Bronx grocery store, but she must make the right choices about her friends, her family, and Moises, the good looking but outspoken boy from the neighborhood